The Impact of Principal Leadership in Guidance and Counseling Services on Self-Development of Senior High School Students - Tumanggor, Salman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2020)
Guidance and counseling services in school should be created as a realistic program to gain student's interests. The effort to improve student's self-development in senior high school can be done through the principal leadership approach. The purpose of studies to determine the role of principal leadership in guidance and counseling services with student's self-development. The participants were selected using purposive sampling from several seniors high school at Banten province, Indonesia. The author uses a descriptive analysis method of correlation with the quantitative approach. 40 items of principal leadership scale (Î± = 0.930) and 120 items of student's self-development (Î± = 0.978) were used to collect the data. The results show there are significant relationships (r2 = 0.495, p < 0.05) and impact (Î² = 0.736, p < 0.05) between principal leadership with student's self-development. The student's self-development is determined by principal leadership in guidance and counseling services.